Methods of identification of priority countries for Slovak economic diplomacy - Macurová, Romana; Peterková, Jana, 1971-; Zemanová, Štěpánka, 1975-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2020)
The aim of the master thesis is to recommend improvements to the current methodology to identify priority markets for Slovak economic diplomacy and apply this methodology to assess Mexico´s potential for becoming a priority market for Slovak economic diplomacy given its diversification strategy. The secondary goal is to identify the opportunities for Slovak exporters in Mexico and find out, using the questionnaires, whether there is an interest from Slovak companies in those sectors to export to Mexico. Lastly, the author will provide recommendations on how to improve the current state of export promotion.
Vedoucí práce: Jana Peterková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses